Effects of guided deep breathing on breathlessness and the breathing pattern in chronic obstructive pulmonary disease: A double-blind randomized control study. Issue 2 (February 2015) - Borge, Christine R.; Mengshoel, Anne Marit; Omenaas, Ernst; Moum, Torbjørn; Ekman, Inger; Lein, Martha P.; Mack, Ulrich; Wahl, Astrid K.
Highlights: Guided breathing show positive effect on perceived change of breathlessness in COPD. Guided breathing show positive effect on breathing pattern in COPD. All groups (i.e. breathing, music, relaxation) show positive improvement of COPD symptoms. All groups may have an efficacy of self-care approaches. Abstract: Objective : To investigate whether guided deep breathing using a device improves breathlessness, quality of life, and breathing pattern in moderate and severe stage of chronic obstructive pulmonary disease (COPD). Methods : In total, 150 patients participated in a double-blind randomized controlled trial in a four-week intervention and a four-month follow-up. Participants were randomized into a guided deep breathing group (GDBG), music listening group (MLG), or sitting still group (SSG). The patients' symptom score using the St George's Respiratory Questionnaire (SGRQ), and a Global Rating Change scale (GRC) was applied to measure breathlessness as primary outcome. The activity score and impact score of SRGQ, and breathing pattern were secondary outcomes. Results : Positive effects of the GDBG were detected in GRC scale in breathlessness at four weeks ( p  = 0.03) with remaining effect compared to MLG ( p  = 0.04), but not to SSG at four months follow-up. GDBG showed positive effect for respiratory rate ( p  < 0.001) at four weeks follow-up. A positive significant change ( p  < 0.05–0.01) was found in all groups of SGRQ symptom score. Conclusion : GDBG had a beneficial effect on respiratory pattern and breathlessness. MLG and SSG also yielded significant improvements. Practice implications : Guided deep breathing may be used as a self-management procedure.